Resveratrol composite material as well as preparation method and application thereof
By loading resveratrol on the mesoporous ceria and modifying hyaluronic acid on its surface, the problems of poor water solubility and low bioavailability of resveratrol are solved, and its efficient anti-inflammatory and antioxidant effects in the body are achieved.
Patent Information
- Application Number
- CN202411858211.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-25
AI Technical Summary
Resveratrol is less bioavailable due to its sensitivity to light and poor water solubleness.
Mesoporous ceria is used as a carrier to load resveratrol inside it, and hyaluronic acid is modified on the surface of mesoporous ceria to improve its water solubility and bioavailability.
It improves the water solubility and bioavailability of resveratrol, enhances its anti-inflammatory and antioxidant capacity, and improves metabolic time and utilization in the body through a targeted release mechanism.
Smart Images

Figure CN119679966A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of biomedicine technology, and in particular to a resveratrol composite material and a preparation method and application thereof. Background Art
[0002] Resveratrol is a polyphenol compound widely found in plants such as grapes, peanuts and mulberries. In recent years, resveratrol has been one of the most widely studied polyphenols. It has the advantages of anti-inflammatory, antioxidant, anti-tumor and promoting digestion. Among them, anti-inflammatory activity is also one of the most widely studied activities of resveratrol. However, it is sensitive to light and has poor water solubility, resulting in low bioavailability. Summary of the invention
[0003] In view of this, the object of the present invention is to provide a resveratrol composite material and a preparation method and application thereof. The resveratrol composite material provided by the present invention has good water solubility and high bioavailability of resveratrol.
[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0005] The invention provides a resveratrol composite material, comprising mesoporous cerium dioxide, resveratrol and hyaluronic acid; the resveratrol is loaded inside the mesoporous cerium dioxide, and the surface of the mesoporous cerium dioxide is modified with a hyaluronic acid layer.
[0006] The present invention also provides a method for preparing the resveratrol composite material described in the above technical solution, comprising the following steps:
[0007] The mesoporous cerium dioxide and the amino-containing modifier undergo a first grafting reaction to obtain amino cerium dioxide;
[0008] The amination of cerium dioxide and resveratrol is subjected to a second grafting reaction to obtain a cerium dioxide / resveratrol composite material;
[0009] The cerium dioxide / resveratrol composite material and hyaluronic acid are subjected to a third grafting reaction to obtain the resveratrol composite material.
[0010] Preferably, the mesoporous ceria has a hollow structure.
[0011] Preferably, the method for preparing mesoporous cerium dioxide comprises the following steps:
[0012] The template, the dispersion stabilizer, the cerium source, the alkaline substance and water are mixed and pre-reacted to obtain a precursor;
[0013] The precursor is sequentially calcined and etched to obtain the mesoporous cerium dioxide;
[0014] The template includes silicon dioxide or carbon spheres;
[0015] The dispersion stabilizer includes polyvinyl pyrrolidone or polyvinyl alcohol;
[0016] The cerium source includes cerium nitrate or cerium acetate;
[0017] The alkaline substance includes hexamethylenetetramine or ammonia water.
[0018] Preferably, the pre-reaction temperature is 90-100° C., and the time is 1-3 hours; the calcination temperature is 500-700° C., and the insulation time is 2-3 hours; and the etching time is 18-24 hours.
[0019] Preferably, the amino-containing modifier comprises γ-aminopropyltriethoxysilane;
[0020] The usage ratio of the mesoporous cerium dioxide and the amino-containing modifier is 50-300 mg: 1-2 mL;
[0021] The first grafting reaction is carried out under reflux conditions, and the time of the first grafting reaction is 10 to 15 hours.
[0022] Preferably, the mass ratio of the amino cerium dioxide to resveratrol is 2:1 to 5:1, and the time of the second grafting reaction is 18 to 30 hours.
[0023] Preferably, the mass ratio of the cerium oxide / resveratrol composite material to hyaluronic acid is 1:0.5 to 1:1.5, and the time of the third grafting reaction is 18 to 24 hours.
[0024] Preferably, the hyaluronic acid is used in the form of a hyaluronic acid activation solution, and the preparation method of the hyaluronic acid activation solution comprises the following steps:
[0025] Mixing hyaluronic acid, EDC, NHS and water for activation to obtain the hyaluronic acid activation solution;
[0026] The molar ratio of hyaluronic acid, EDC and NHS is 1:2:2;
[0027] The activation temperature is room temperature and the activation time is 2 to 4 hours.
[0028] The present invention also provides the use of the resveratrol composite material described in the above technical solution or the resveratrol composite material prepared by the preparation method described in the above technical solution in the preparation of anti-inflammatory drugs.
[0029] The invention provides a resveratrol composite material.
[0030] It has the following advantages:
[0031] (1) Cerium dioxide (CeO 2 ) nanoparticles are a new type of nanozyme with Ce 3+ and Ce 4+ Rapid and reversible conversion can occur, making cerium dioxide nanozymes (CeO 2 NPs) have both antioxidant and pro-oxidant properties. 2 NPs can be used to treat diseases such as cancer, inflammation, and tissue damage, and have a variety of potentials. Moreover, compared with other metal materials, CeO 2 NPs have relatively low toxicity to mammalian cells, excellent biocompatibility, and regenerative catalytic performance. The present invention uses mesoporous ceria as a carrier. Based on its mesoporous structure, resveratrol can be loaded inside the mesoporous ceria, achieving synergistic effects between ceria nanozymes and active polyphenol resveratrol, giving the composite material excellent anti-inflammatory and antioxidant capabilities; at the same time, resveratrol is loaded inside the mesoporous ceria, overcoming the shortcomings of poor water solubility and low bioavailability of resveratrol.
[0032] (2) The resveratrol composite material of the present invention is modified with hyaluronic acid on the surface of mesoporous ceria, and hyaluronic acid is not easily digested in the stomach, and can also specifically target the CD44 receptor overexpressed on the surface of inflammatory cells, thereby enhancing the uptake of ceria and resveratrol by inflammatory cells. In other words, connecting hyaluronic acid on the surface of mesoporous ceria can not only increase the stability of the resveratrol composite material, but also make the resveratrol composite material targeted, so that it can better play a role in the inflammatory site.
[0033] (3) In the resveratrol composite material of the present invention, both cerium dioxide and resveratrol have the ability to scavenge active oxygen, and the synergistic effect of the two enhances the antioxidant and anti-inflammatory capabilities of the composite material; the connection with hyaluronic acid enables the composite material to release drugs (cerium dioxide and resveratrol) in a targeted manner, thereby increasing the metabolic time of resveratrol in the body and precisely acting on the inflammatory site, which not only improves the solubility of resveratrol in the body and enhances its anti-inflammatory and antioxidant capabilities, but also enhances the uptake of resveratrol by the inflammatory site and improves its utilization in the body.
[0034] (4) The resveratrol composite material provided by the present invention has the activity of simulating catalase, peroxidase, and superoxide dismutase, and can reversibly remove active oxygen such as hydrogen peroxide, peroxide, superoxide, and hydroxyl free radicals with super strong activity; it has good stability and good biosafety. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 Mesoporous cerium dioxide (CeO 2 ) and resveratrol composites (Res / HA-CeO 2) transmission electron micrograph;
[0036] Figure 2 Mesoporous cerium dioxide (CeO 2 ), resveratrol-loaded cerium dioxide (CeO 2 / Res) and resveratrol composites (Res / HA-CeO 2 ) particle size distribution diagram;
[0037] Figure 3 HA, CeO 2 、CeO 2 -NH 2 、CeO 2 -HA and Res / HA-CeO 2 Zeta potential diagram;
[0038] Figure 4 CeO 2 and Res / HA-CeO 2 XRD pattern of
[0039] Figure 5 Res / HA-CeO 2 XPS full spectrum;
[0040] Figure 6 CeO 2 and Res / HA-CeO 2 High-resolution XPS spectrum of Ce 3d;
[0041] Figure 7 HA, Res, CeO 2 and Res / HA-CeO 2 Fourier transform infrared spectrum of
[0042] Figure 8 CeO 2 、Res / CeO 2 and Res / HA-CeO 2 Antioxidant activity diagram of
[0043] Fig. 9 CeO 2 、Res / CeO 2 and Res / HA-CeO 2 Cytotoxicity profile measured by CCK8 assay;
[0044] Fig.10 CeO 2 、Res / CeO 2 and Res / HA-CeO 2 The ability to scavenge reactive oxygen species was determined by the DCFH-DA probe method;
[0045] Fig.11 CeO 2 、Res / CeO 2 and Res / HA-CeO 2 Effects of qPCR on the expression of inflammatory factors;
[0046] Fig.12 CeO 2 、Res / CeO 2 and Res / HA-CeO 2 Effect diagram of anti-inflammatory factor expression by qPCR method;
[0047] Fig.13 CeO 2 、Res / CeO 2 and Res / HA-CeO 2 Effects on M1 macrophage polarization measured by flow cytometry;
[0048] Fig.14 CeO 2 、Res / CeO 2 and Res / HA-CeO 2 Effects on M2 macrophage polarization as determined by flow cytometry. DETAILED DESCRIPTION
[0049] The invention provides a resveratrol composite material, comprising mesoporous cerium dioxide, resveratrol and hyaluronic acid; the resveratrol is loaded inside the mesoporous cerium dioxide, and the surface of the mesoporous cerium dioxide is modified with a hyaluronic acid layer.
[0050] The resveratrol composite material provided by the present invention comprises mesoporous cerium dioxide, and the mesoporous cerium dioxide preferably has a hollow structure.
[0051] The resveratrol composite material provided by the present invention comprises resveratrol, and the resveratrol is loaded inside the mesoporous cerium dioxide.
[0052] The resveratrol composite material provided by the invention comprises hyaluronic acid, and the surface of the mesoporous cerium dioxide is modified with a hyaluronic acid layer.
[0053] The present invention also provides a method for preparing the resveratrol composite material described in the above technical solution, comprising the following steps:
[0054] The mesoporous cerium dioxide and the amino-containing modifier undergo a first grafting reaction to obtain amino cerium dioxide;
[0055] The amination of cerium dioxide and resveratrol is subjected to a second grafting reaction to obtain a cerium dioxide / resveratrol composite material;
[0056] The cerium dioxide / resveratrol composite material and hyaluronic acid are subjected to a third grafting reaction to obtain the resveratrol composite material.
[0057] Unless otherwise specified, the raw materials used in the present invention are preferably commercially available products.
[0058] The mesoporous cerium dioxide of the present invention and the amino-containing modifier undergo a first grafting reaction to obtain the amino cerium dioxide.
[0059] In the present invention, the mesoporous cerium dioxide preferably has a hollow structure. In the present invention, the preparation method of the mesoporous cerium dioxide comprises the following steps:
[0060] The template, the dispersion stabilizer, the cerium source, the alkaline substance and water are mixed and pre-reacted to obtain a precursor;
[0061] The precursor is calcined and etched in sequence to obtain the mesoporous cerium dioxide.
[0062] The present invention mixes a template, a dispersion stabilizer, a cerium source, an alkaline substance and water, performs a pre-reaction, and obtains a precursor. In the present invention, the template preferably includes silicon dioxide or carbon spheres, and more preferably silicon dioxide. In the present invention, the particle size of the silicon dioxide is preferably 90nm to 105nm, and the particle size of the carbon spheres is preferably 100nm to 120nm. In the present invention, the dispersion stabilizer preferably includes polyvinyl pyrrolidone (PVP) or polyvinyl alcohol, and more preferably polyvinyl pyrrolidone (PVP). In the present invention, the cerium source preferably includes cerium nitrate or cerium acetate, and more preferably cerium nitrate, and more preferably cerium nitrate hexahydrate (Ce(NO 3 ).6H 2 O). In the present invention, the alkaline substance preferably includes hexamethylenetetramine (HMTA) or ammonia water; the alkaline substance is preferably used in the form of an alkaline substance aqueous solution, and the concentration of the alkaline substance aqueous solution is preferably 5 mol / L.
[0063] In the present invention, the mass ratio of the template and the dispersion stabilizer is preferably 0.1:1 to 0.1:1.5, and is specifically preferably 0.1:1, 0.1:1.1, 0.1:1.2, 0.1:1.3, 0.1:1.4 or 0.1:1.5. In the present invention, the dosage ratio of the template and the cerium source is preferably 0.1g:2.5 to 5mmol, and is further preferably 0.1g:2.5mmol, 0.1g:3mmol, 0.1g:3.5mmol, 0.1g:4mmol, 0.1g:4.5mmol or 0.1g:5mmol. In the present invention, the molar ratio of the cerium source and the alkaline substance is preferably 1:1 to 2, and is specifically preferably 1:1, 1:1.5 or 1:2. In the present invention, in the mixed solution obtained by mixing, the concentration of the cerium source is preferably 0.005 to 0.1mol / L, and is further preferably 0.05mol / L.
[0064] In the present invention, the mixing of the template, dispersion stabilizer, cerium source, alkaline substance and water preferably includes the following steps: dispersing and mixing the template, dispersion stabilizer and water, and then adding the cerium source and alkaline substance; the dispersing and mixing is preferably carried out under the condition of an oil bath, and the temperature of the oil bath is preferably 90-100°C, and more preferably 95°C.
[0065] In the present invention, the temperature of the pre-reaction is preferably 90-100°C, more preferably 95°C; the time is preferably 1-3h, more preferably 2h; the pre-reaction is preferably carried out under stirring. After the pre-reaction, the present invention preferably further comprises: centrifuging the obtained pre-reaction liquid to collect the precipitate; washing and drying the precipitate in sequence to obtain the precursor; the centrifugal speed is preferably 5000-7000rpm, more preferably 6000rpm; the time is preferably 2-10min, more preferably 5min; the washing reagent is preferably deionized water, and the number of washings is preferably 3 times; the drying temperature is preferably 60°C, and the time is preferably 10-20h, more preferably 12h.
[0066] After obtaining the precursor, the present invention sequentially calcines and etches the precursor to obtain the mesoporous cerium dioxide. In the present invention, the calcination temperature is preferably 500-700°C, more preferably 600°C, specifically preferably 500°C, 550°C, 600°C, 650°C or 700°C; the holding time is preferably 2-3h. In the present invention, the calcination is preferably carried out in a muffle furnace.
[0067] In the present invention, when the template is silicon dioxide, the etching agent is preferably an inorganic alkaline solution, the inorganic alkaline solution is preferably a sodium hydroxide solution, and the concentration of the sodium hydroxide solution is preferably 2 mol / L. In the present invention, the amount ratio of the solid material obtained after calcination and the inorganic alkaline solution is preferably 0.1g:40mL. In the present invention, the etching temperature is preferably room temperature, the time is preferably 18 to 24h, and more preferably 20h, and the etching is preferably carried out under stirring. After the etching, the present invention preferably further includes: centrifuging the obtained etching liquid to obtain a solid, washing and drying the solid in turn to obtain the mesoporous cerium dioxide. In the present invention, the centrifugal speed is preferably 5000-7000rpm, more preferably 5500-6500rpm, and more preferably 6000rpm; the time is preferably 2-10min, and more preferably 5min; the washing includes alcohol washing and water washing in sequence, the alcohol washing reagent is preferably anhydrous ethanol, the number of alcohol washings is preferably 3 times, and the number of water washings is preferably 3 times; the drying temperature is preferably 60°C, and the time is preferably 10-20h.
[0068] In the present invention, when the template is a carbon sphere, it is preferably not etched; the carbon sphere can be removed during the calcination process.
[0069] In the present invention, the amino-containing modifier preferably includes γ-aminopropyltriethoxysilane (APTES). In the present invention, the amount ratio of the mesoporous cerium dioxide and the amino-containing modifier is preferably 50-300 mg: 1-2 mL, and is specifically preferably 50 mg: 1 mL, 50 mg: 1.5 mL, 100 mg: 1 mL, 100 mg: 1.5 mL, 150 mg: 1 mL, 150 mg: 1.25 mL, 200 mg: 1 mL, 200 mg: 1.5 mL or 300 mg: 1 mL. In the present invention, the medium of the first grafting reaction is preferably ethanol, and is further preferably anhydrous ethanol. In the present invention, the amount ratio of the mesoporous cerium dioxide and ethanol is preferably 1-5 mg: 1 mL, and is specifically preferably 1 mg: 1 mL, 2 mg: 1 mL, 3 mg: 1 mL, 4 mg: 1 mL or 5 mg: 1 mL.
[0070] In the present invention, the first grafting reaction is preferably carried out under reflux conditions, and the time of the first grafting reaction is preferably 10 to 15 hours, more preferably 12 hours. In the present invention, the first grafting reaction is preferably carried out under water bath heating conditions.
[0071] In the present invention, the first grafting reaction of mesoporous ceria and amino-containing modifier preferably comprises the following steps: dispersing mesoporous ceria into the medium of the first grafting reaction, heating to reflux in a water bath, adding amino-containing modifier, and performing the first grafting reaction.
[0072] After the first grafting reaction, the present invention preferably further comprises: centrifuging the obtained first grafting reaction liquid to obtain a precipitate; washing and drying the precipitate in sequence to obtain the amino cerium dioxide; the centrifugal speed is preferably 5000-7000rpm, more preferably 6000rpm, the time is preferably 2-10min, more preferably 5min; the washing reagent is preferably deionized water.
[0073] After obtaining the aminated cerium dioxide, the aminated cerium dioxide and resveratrol of the present invention are subjected to a second grafting reaction to obtain a cerium dioxide / resveratrol composite material (Res / CeO 2 ).
[0074] In the present invention, the mass ratio of the aminated cerium dioxide to resveratrol is preferably 2:1 to 5:1, specifically preferably 2:1, 2.5:1, 3:1, 3.3:1, 3.5:1, 4:1, 4.5:1 or 5:1. In the present invention, the medium of the second grafting reaction is preferably ethanol, more preferably anhydrous ethanol.
[0075] In the present invention, the temperature of the second grafting reaction is preferably room temperature, the time is preferably 18 to 30 hours, and more preferably 24 hours. In the present invention, the second grafting reaction is preferably carried out under stirring.
[0076] In the present invention, the second grafting reaction of the aminated cerium dioxide and resveratrol preferably comprises the following steps: dispersing the aminated cerium dioxide in ethanol, and then adding resveratrol to carry out the second grafting reaction.
[0077] After the second grafting reaction, the present invention preferably further comprises: centrifuging the obtained second medium reaction liquid to obtain a precipitate, washing and drying the precipitate in sequence to obtain the cerium oxide / resveratrol composite material. In the present invention, the centrifugal speed is preferably 5000-7000 rpm, more preferably 6000 rpm, the time is preferably 1-10 min, more preferably 5 min; the washing reagent is preferably deionized water.
[0078] After obtaining the cerium oxide / resveratrol composite material, the present invention conducts a third grafting reaction on the cerium oxide / resveratrol composite material and hyaluronic acid to obtain the resveratrol composite material, which is recorded as Res / HA-CeO 2 .
[0079] In the present invention, the mass ratio of the cerium oxide / resveratrol composite material to hyaluronic acid is preferably 1:0.5 to 1:1.5, and is particularly preferably 1:0.5, 1:0.75, 1:1 or 1:1.5. In the present invention, the hyaluronic acid is preferably used in the form of a hyaluronic acid activation solution, and the preparation method of the hyaluronic acid activation solution preferably comprises the following steps: mixing hyaluronic acid, EDC, NHS and water, activating to obtain the hyaluronic acid activation solution; the molar ratio of the hyaluronic acid, EDC and NHS is preferably 1:2:2; the dosage ratio of the hyaluronic acid and water is preferably 10 mg:50 mL. In the present invention, the activation temperature is preferably room temperature, and the time is preferably 2 to 4 hours.
[0080] In the present invention, the temperature of the third grafting reaction is preferably room temperature, and the time is preferably 18 to 24 hours; the third grafting reaction is preferably carried out under stirring.
[0081] After the third grafting reaction, the present invention preferably further comprises: centrifuging the obtained third grafting reaction liquid to obtain a precipitate, washing and drying the precipitate in sequence to obtain the resveratrol composite material. In the present invention, the centrifugal speed is preferably 5000-7000 rpm, more preferably 6000 rpm, the time is preferably 1-10 min, more preferably 5 min; the washing reagent is preferably deionized water.
[0082] The present invention also provides the use of the resveratrol composite material described in the above technical solution or the resveratrol composite material prepared by the preparation method described in the above technical solution in the preparation of anti-inflammatory drugs.
[0083] The present invention does not specifically limit the application mode of the resveratrol composite material, and those skilled in the art can configure it according to actual needs.
[0084] The resveratrol composite material provided by the present invention, its preparation method and application are described in detail below in conjunction with the examples, but they should not be construed as limiting the protection scope of the present invention.
[0085] Example 1
[0086] Preparation method of cerium dioxide nanoparticles loaded with resveratrol
[0087] Preparation method of mesoporous cerium dioxide: 0.1g dry SiO 2 (particle size of 100nm±4.5nm) and 1g of PVP were ultrasonically dispersed in 40mL of deionized water and heated in an oil bath at 95℃. 5mL of 0.5mol / L Ce(NO 3 ).6H 2O solution and 5 mL of 0.5 mol / L HMTA solution were added to the above solution in sequence and stirred for 2 h. The precipitate was washed 3 times with deionized water by centrifugation at 6000 rpm for 5 min and dried at 60 °C overnight to obtain a precursor. The precursor was placed in a muffle furnace and calcined at 600 °C for 2 h to obtain SiO 2 @CeO 2 Then, 0.1 g of SiO 2 @CeO 2 Disperse into 40mL 2mol / L NaOH solution to etch SiO 2 The template was stirred at room temperature for 20 h, then centrifuged at 6000 rpm for 5 min, and the precipitate was washed with anhydrous ethanol and water for 3 times each, and dried at 60 ° C overnight to obtain mesoporous cerium dioxide (CeO 2 ).
[0088] Preparation method of cerium dioxide nanoparticles loaded with hyaluronic acid: 50 mg of mesoporous cerium dioxide (CeO 2 ) was evenly dispersed in 50 mL of anhydrous ethanol to obtain a 1 mg / mL cerium dioxide dispersion, heated in a water bath to 75 ° C, 1 mL of APTES was added, heated to reflux for 12 h, and centrifuged at 6000 rpm for 5 min to obtain a precipitate, which was washed with deionized water and dried to obtain aminated cerium dioxide (CeO 2 -NH 2 10 mg of hyaluronic acid was added to 50 mL of deionized water, stirred evenly, and then EDC and NHS were added at a molar ratio of 1:2:2 to hyaluronic acid, and activated at room temperature for 120 min to obtain hyaluronic acid activation solution; then 40 mg of CeO prepared above was added to 2 -NH 2 The mixture was added to the hyaluronic acid activation solution and stirred for 24 h. After the reaction, the mixture was centrifuged at 6000 rpm for 5 min. The collected precipitate was washed and dried at 60 °C overnight to obtain hyaluronic acid-loaded cerium dioxide nanoparticles (HA-CeO 2 ).
[0089] Preparation method of resveratrol composite material: 50 mg of mesoporous cerium dioxide (CeO 2 ) was evenly dispersed in 50 mL of anhydrous ethanol to obtain a 1 mg / mL cerium dioxide dispersion, heated in a water bath to 75 ° C, 1 mL of APTES was added, heated to reflux for 12 h, and centrifuged at 6000 rpm for 5 min to obtain a precipitate, which was washed with deionized water and dried to obtain aminated cerium dioxide (CeO 2 -NH 220 mg of aminated cerium dioxide was dispersed in 10 mL of anhydrous ethanol, and resveratrol was added to make the concentration of resveratrol 1 mg / mL. The mixture was stirred for 24 h, centrifuged, washed and dried to obtain a cerium dioxide / resveratrol composite material (Res / CeO 2 Next, 10 mg of hyaluronic acid was added to 50 mL of deionized water, stirred evenly, and then EDC and NHS were added at a molar ratio of 1:2:2 to hyaluronic acid, and activated at room temperature for 120 min to obtain hyaluronic acid activation solution; then 10 mg of Res / CeO 2 The mixture was added to the hyaluronic acid activation solution and stirred for 24 h. After the reaction, the mixture was centrifuged at 6000 rpm for 5 min. The collected precipitate was washed and dried at 60 °C overnight to obtain a resveratrol composite material (Res / HA-CeO 2 ).
[0090] Performance Testing
[0091] (1) Physical and chemical characterization test
[0092] Figure 1 Mesoporous cerium dioxide (CeO 2 ) and Res / HA-CeO 2 Transmission electron micrograph of Figure 1 It can be seen that the mesoporous cerium dioxide nanoparticles have a round hollow structure. 2 The average particle size is about 120nm ( Figure 1 Left figure), Res / HA-CeO 2 The average particle size of the composite material is about 150nm (see Figure 1 (right picture in the figure).
[0093] The particle size was further measured by DLS. Figure 2 , Figure 2 Mesoporous cerium dioxide (CeO 2 ), resveratrol (Res) loaded cerium dioxide (Res / CeO 2 ) and resveratrol composites (Res / HA-CeO 2 ) particle size diagram, from Figure 2 It can be seen that after loading Res, the particle size of the nanoparticles has hardly changed (see Figure 2 b), indicating that resveratrol is loaded inside the mesoporous cerium dioxide, while in CeO 2 The particle size increased significantly after HA was attached to the surface (see Figure 2 c) in the figure indicates that the hyaluronic acid layer is located on the surface of the mesoporous ceria.
[0094] The potential of each sample was measured and the results were as follows: Figure 3As shown, Figure 3 HA, CeO 2 、CeO 2 -NH 2 、CeO 2 -HA and Res / HA-CeO 2 Zeta potential diagram, from Figure 3 It can be seen that CeO, which is negatively charged 2 (-20.07±1.35mV) The amino groups formed CeO 2 -NH 2 , CeO 2 -NH 2 The potential of CeO was positive (9.14±0.80mV). After HA was further modified on the surface, the 2 The Zeta potential of -HA was negative (15.77±0.19 mV), which was probably due to the binding with HA, leading to the change of potential.
[0095] Determination of the loading amount and encapsulation efficiency of nanoparticles for Res: Disperse the aminated cerium dioxide in 10 mL of anhydrous ethanol, and then add resveratrol so that the concentration of aminated cerium dioxide in the system is 2 mg / mL and the concentration of resveratrol is 1 mg / mL. After stirring for 12 hours, centrifuge and absorb the supernatant, dilute it 10, 15 and 20 times, and use a spectrophotometer to measure its absorbance at 306 nm, calculate the drug loading amount and encapsulation efficiency, and the drug loading amount and encapsulation efficiency are measured to be 6.17% ± 0.32% and 65.01% ± 3.41%, respectively. The encapsulation efficiency and loading rate can also indicate that resveratrol is loaded inside the mesoporous cerium dioxide.
[0096] CeO was determined by XRD at a scattering angle of 0-80° 2 and Res / HA-CeO 2 The crystal structure of Figure 4 As shown, Figure 4 CeO 2 and Res / HA-CeO 2 XRD pattern of Figure 4 It can be seen that after loading Res and connecting HA, CeO 2 The crystal structure has not changed.
[0097] Figure 5 Res / HA-CeO 2 The XPS spectrum of Figure 5 It can be seen that in Res / HA-CeO 2 In the XPS results, the peaks of Ce 3d, O 1s, N 1s and C1s were observed, which indicated that HA was successfully connected to CeO 2surface.
[0098] Figure 6 CeO 2 and Res / HA-CeO 2 High-resolution XPS spectrum of Ce 3d, Figure 6 The peaks at 885 and 904 eV are Ce. 3+ The peaks at 882.1, 898.5, 9009.9, 906.4 and 916.4 eV are Ce 4+ , Ce 3+ The content of Ce is 20.59%, 4+ The content of Res / HA-CeO 2 The mixed valence state proves that it has good catalytic performance.
[0099] In order to verify the 2 The successful connection of HA, Res, CeO 2 and Res / HA-CeO 2 Fourier infrared spectroscopy was performed, and the results were as follows Figure 7 As shown, Figure 7 HA, Res, CeO 2 and Res / HA-CeO 2 The Fourier infrared spectrum of Figure 7 As shown, Res / HA-CeO 2 At 3324cm -1 The peak at is the phenol absorption peak of Res, and the characteristic peak of the C=C group in Res is 1596cm -1 The tensile vibrations appearing near the surface indicate the successful loading of Res. 2 At 1632cm -1 The peak at 1416 cm is the characteristic absorption peak of the amide bond formed by the combination of the carboxyl group and the amino group of HA. -1 The characteristic absorption peak of the -COOH group of HA appears at , proving the successful connection of HA.
[0100] (2) Antioxidant activity determination.
[0101] The CeO 2 , Res / CeO 2 and Res / HA-CeO 2 DPPH and ·OH scavenging activity as well as SOD and CAT enzyme activities.
[0102] In order to evaluate CeO 2 、Res / CeO 2 and Res / HA-CeO2 The scavenging activities of DPPH and ·OH and the enzyme activities of SOD and CAT were determined using DPPH, ·OH, SOD and CAT detection kits. 0.01, 0.025, 0.05, 0.075, 0.1 mg / mL CeO 2 、Res / CeO 2 and Res / HA-CeO 2 The solution was tested according to the instructions of the kit, and its antioxidant capacity was determined based on its ultraviolet absorbance. Figure 8 .
[0103] Figure 8 CeO 2 , Res / CeO 2 and Res / HA-CeO 2 The antioxidant activity diagram is shown in Figure 1, where a is the scavenging activity of ·OH, b is the scavenging activity of DPPH, c is the SOD enzyme activity, and d is the CAT enzyme activity. Figure 8 As shown in a and b, CeO 2 It showed obvious active oxygen scavenging ability and concentration dependence. With the increase of concentration, the scavenging rate also increased gradually. 2 and Res / HA-CeO 2 The results are better than CeO 2 This may be due to the fact that natural Res polyphenols have the ability to scavenge active oxygen, and the synergistic effect of the two enhances its scavenging ability. The above results all prove that the composite material has a significant ability to scavenge active oxygen. Figure 8 As can be seen from c and d in Figure 3, all three materials have good SOD and CAT enzyme activities, among which Res / CeO 2 and Res / HA-CeO 2 There was no significant difference in the SOD and CAT enzyme activities, which may be attributed to the Ce 3+ The content of CeO 2 The higher SOD and CAT enzyme activities may be attributed to the antioxidant properties of the loaded natural polyphenol Res itself.
[0104] (3) Cytotoxicity assay
[0105] In order to verify the safe concentration of the material for cells, the CCK-8 method was used for verification.
[0106] Macrophages were cultured at a rate of 2×10 5 The cells were uniformly inoculated in a 96-well plate and cultured at 37 °C for 24 h. Then, CeO at concentrations of 0.025, 0.05, 0.075, 0.1, 0.2, and 0.4 mg / mL were added. 2 、Res / CeO2 and Res / HA-CeO 2 Incubate for 24 hours, with 6 parallels in each group. After incubation in the incubator for 24 hours, add 100 μL of CCK-8 solution per milliliter of culture medium to a 96-well plate. After incubation for 30 minutes, use an enzyme reader to measure the absorbance at 450 nm. The results are as follows: Fig. 9 As shown, Fig. 9 CeO 2 , Res / CeO 2 and Res / HA-CeO 2 The cytotoxicity chart measured by CCK8 method, from Fig. 9 It can be seen that CeO 2 、Res / CeO 2 and Res / HA-CeO 2 When the concentration reaches 200μg / mL, the cell viability is still high, which proves that the material has good safety for cells.
[0107] (4) Determination of the ability to scavenge reactive oxygen species in vitro.
[0108] Raw 264.7 cells were cultured at 2 × 10 5 The cells were seeded at a density of 500 ng / mL and cultured overnight in a 6-well plate. 2 、Res / CeO 2 and Res / HA-CeO 2 After 24 hours of co-intervention, cells not stimulated by LPS were used as the control group. Then, the ROS fluorescent probe DCFH-DA (50 μM) was added to the wells and incubated for 30 minutes to label the ROS in the cells. The ROS fluorescence images were taken using a laser confocal scanning microscope (CLSM). Fig.10 As shown, Fig.10 CeO 2 、Res / CeO 2 and Res / HA-CeO 2 The ability to scavenge reactive oxygen species was determined by the DCFH-DA probe method. Fig.10 It can be seen that after LPS induction, the fluorescence was significantly enhanced compared with the normal control group, while after treatment with various materials, the fluorescence was significantly weakened, proving that the intracellular reactive oxygen species were significantly reduced; and it was found that Res / HA-CeO 2 The treatment group was significantly better than CeO 2 and Res / CeO 2 group, which may be due to the targeting effect of HA, enhancing the cellular uptake of the material, thereby increasing the active oxygen scavenging effect.
[0109] (5) Determination of the effects on the expression of inflammatory and anti-inflammatory factors.
[0110] In order to verify the anti-inflammatory ability of the material in vitro, the expression of inflammatory factors (TNF-α, IL-6, IL-1β and INOS) and anti-inflammatory factors (TGF-β, Arg-1 and IL-10) was measured by qPCR.
[0111] First, add 1mL Rz lysis buffer to each well of the 6-well plate and scrape it with a scraper. Then collect the cell lysate into a 1.5mL tube, add 200μL chloroform to each tube, mix well, place at room temperature for 3min, and centrifuge at 4℃12000rpm for 10min. Take the supernatant, add 0.5 times the volume of anhydrous ethanol to mix well, transfer to the adsorption column CR3, centrifuge at 4℃12000rpm for 30s, discard the waste liquid in the collection tube, add 500μL deproteinization solution RD, and centrifuge at 4℃12000rpm for 30s. Add 500μL rinse solution RW to the adsorption column CR3, let stand at room temperature for 2min, centrifuge at 4℃12000rpm for 30s, and discard the waste liquid. Place the adsorption column in a 2mL collection tube, centrifuge at 4℃12000rpm for 2min, and remove the residual liquid. Transfer the adsorption column CR3 to a new 1.5mL centrifuge tube and add 30μLRNase-Free ddH 2 O, place at room temperature for 2 minutes, and centrifuge at 4°C 12000rpm for 2 minutes. Next, reverse transcription was performed to prevent RNA degradation. Take 10 μL of the above extracted RNA sample, add 4 μL Max, and supplement with ddH 2 0 to 20 μL, set the reaction temperature and reaction time for reverse transcription. Finally, the obtained cDNA was subjected to quantitative PCR, and 1 μL cDNA, 10 μL SYBR Green, 0.4 μL upstream primer (see Table 1), 0.4 μL downstream primer (see Table 1), and 8.2 μL sterile water were added to the eight strip tubes, and the total reaction system was 20 μL.
[0112] After the reaction solution was evenly mixed, the eight-tube PCR was placed in a real-time quantitative PCR instrument, and the parameters were set as pre-denaturation at 95°C for 180s; denaturation at 95°C for 30s, annealing at 60°C for 30s, extension at 72°C for 30s, and 40 cycles for quantitative PCR reaction.
[0113] Table 1 Primer sequences
[0114]
[0115] Fig.11 CeO 2 、Res / CeO 2 and Res / HA-CeO 2 The effect of qPCR on the expression of inflammatory factors, Fig.12 CeO 2 、Res / CeO 2 and Res / HA-CeO 2 Effect of qPCR on the expression of anti-inflammatory factors. Fig.11 It can be seen that the inflammatory factors related to M1 macrophages include TNF-α, IL-6, IL-1β and INOS. After LPS induction, the expression of related inflammatory factors mRNA increased significantly, indicating that the in vitro inflammatory model was successfully established. 2 、Res / CeO 2 and Res / HA-CeO 2 The experimental group could significantly reduce the expression of inflammatory factors, among which Res / CeO 2 and Res / HA-CeO 2 The inhibitory effect is better than CeO 2 The effect is obvious, proving that Res and CeO 2 can work synergistically; and it was also found that Res / HA-CeO 2 The effect is better than Res / CeO 2 The effect is more obvious, which may be due to the presence of HA increasing the cellular uptake of the material, thus showing a better effect.
[0116] from Fig.12 It can be seen that for the anti-inflammatory factors TGF-β, Arg-1 and IL-10, the negative control group stimulated by LPS failed to increase their expression compared with the blank control group. 2 、Res / CeO 2 and Res / HA-CeO 2 Both significantly increased the mRNA expression of Arg-1 and TGF-β. However, for the IL-10 gene, CeO 2 The effect of the group was not significant.
[0117] (6) Determine the effect on macrophage phenotype.
[0118] M1 macrophages are pro-inflammatory macrophages that secrete inflammatory factors, while M2 macrophages are anti-inflammatory macrophages that secrete anti-inflammatory factors. 2 、Res / CeO 2 and Res / HA-CeO 2 ) on M1 and M2 phenotypes can become an important indicator for evaluating the anti-inflammatory activity of materials.
[0119] RAW264.7 at 5×10 6 The cells in the 6-well plate were inoculated with LPS, CeO2 、Res / CeO 2 and Res / HA-CeO 2 Stimulation. The cells were washed with PBS solution containing 2% FBS, and then incubated with anti-mouse CD206 (M2 type) and CD86 (M1 type) for 30 min at room temperature in the dark, and then further incubated with fluorescent secondary antibodies for 30 min. The expression of macrophage surface markers was measured by flow cytometry through fluorescence detection, and FlowJo v 10.4.0 was used to analyze the data. The results are shown in Fig.13 and Fig.14 shown.
[0120] Fig.13 CeO 2 、Res / CeO 2 and Res / HA-CeO 2 The effect on M1 macrophage polarization was determined by flow cytometry. Fig.14 CeO 2 、Res / CeO 2 and Res / HA-CeO 2 The effect on M2 macrophage polarization was determined by flow cytometry. Fig.13 It can be seen that after LPS induction, the expression of CD86 increased significantly, reaching 98%, while after CeO 2 、Res / CeO 2 and Res / HA-CeO 2 After treatment, CD86 expression was significantly decreased and Res / CeO 2 and Res / HA-CeO 2 The effect is significantly better than CeO 2 , further confirming that Res and CeO 2 Inhibitory effect on M1 macrophages. Fig.14 It can be seen that after Res / CeO 2 and Res / HA-CeO 2 The expression of CeO was significantly increased after treatment, but 2 There was little difference between the treated group and the LPS group and the control group, which proved that M2 cells may be mainly promoted by natural polyphenol Res.
[0121] Example 2
[0122] The preparation method of mesoporous cerium dioxide is the same as that in Example 1.
[0123] 100 mg of mesoporous cerium dioxide (CeO 2) was evenly dispersed in 50 mL of anhydrous ethanol to obtain a 2 mg / mL cerium dioxide dispersion, heated in a water bath to 75 ° C, added with 1 mL of APTES, heated under reflux for 12 h, and centrifuged at 6000 rpm for 5 min to obtain a precipitate, which was washed with deionized water and dried to obtain aminated cerium dioxide (CeO 2 -NH 2 50 mg of aminated cerium dioxide was dispersed in 10 mL of anhydrous ethanol, and resveratrol was added to make the concentration of resveratrol 1 mg / mL. The mixture was stirred for 24 h, centrifuged, washed and dried to obtain a cerium dioxide / resveratrol composite material (Res / CeO 2 Next, 15 mg of hyaluronic acid was added to 50 mL of deionized water, stirred evenly, and then EDC and NHS were added at a molar ratio of 1:2:2 to hyaluronic acid, and activated at room temperature for 150 min to obtain hyaluronic acid activation solution; then 20 mg of Res / CeO 2 The mixture was added to the hyaluronic acid activation solution and stirred for 24 h. After the reaction, the mixture was centrifuged at 6000 rpm for 5 min. The collected precipitate was washed and dried at 60 °C overnight to obtain a resveratrol composite material (Res / HA-CeO 2 ).
[0124] Example 3
[0125] The preparation method of mesoporous cerium dioxide is the same as that in Example 1.
[0126] 150 mg of mesoporous cerium dioxide (CeO 2 ) was evenly dispersed in 50 mL of anhydrous ethanol to obtain a 3 mg / mL cerium dioxide dispersion. After heating to 75 °C in a water bath, 1.25 mL of APTES was added. After heating and refluxing for 12 h, the mixture was centrifuged at 6000 rpm for 5 min. The precipitate was washed with deionized water and dried to obtain aminated cerium dioxide (CeO 2 -NH 2 100 mg of aminated cerium dioxide was dispersed in 10 mL of anhydrous ethanol, and resveratrol was added to make the concentration of resveratrol 3 mg / mL. The mixture was stirred for 24 h, centrifuged, washed and dried to obtain a cerium dioxide / resveratrol composite material (Res / CeO 2 Next, 20 mg of hyaluronic acid was added to 50 mL of deionized water, stirred evenly, and then EDC and NHS were added at a molar ratio of 1:2:2 to hyaluronic acid, and activated at room temperature for 180 min to obtain hyaluronic acid activation solution; then 40 mg of Res / CeO 2 The mixture was added to the hyaluronic acid activation solution and stirred for 24 h. After the reaction, the mixture was centrifuged at 6000 rpm for 5 min. The collected precipitate was washed and dried at 60 °C overnight to obtain a resveratrol composite material (Res / HA-CeO2 ).
[0127] Example 4
[0128] The preparation method of mesoporous cerium dioxide is the same as that in Example 1.
[0129] 200 mg of mesoporous cerium dioxide (CeO 2 ) was evenly dispersed in 50 mL of anhydrous ethanol to obtain a 4 mg / mL cerium dioxide dispersion, heated in a water bath to 75 ° C, added with 2 mL of APTES, heated under reflux for 12 h, centrifuged at 6000 rpm for 5 min, and the precipitate was washed with deionized water and dried to obtain aminated cerium dioxide (CeO 2 -NH 2 150 mg of aminated cerium dioxide was dispersed in 10 mL of anhydrous ethanol, and resveratrol was added to make the concentration of resveratrol 3.7 mg / mL. The mixture was stirred for 24 h, centrifuged, washed and dried to obtain a cerium dioxide / resveratrol composite material (Res / CeO 2 Next, 25 mg of hyaluronic acid was added to 50 mL of deionized water, stirred evenly, and then EDC and NHS were added at a molar ratio of 1:2:2 to hyaluronic acid, and activated at room temperature for 200 min to obtain hyaluronic acid activation solution; then 50 mg of Res / CeO 2 The mixture was added to the hyaluronic acid activation solution and stirred for 24 h. After the reaction, the mixture was centrifuged at 6000 rpm for 5 min. The collected precipitate was washed and dried at 60 °C overnight to obtain a resveratrol composite material (Res / HA-CeO 2 ).
[0130] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A resveratrol composite material, characterized in that: The invention comprises mesoporous cerium dioxide, resveratrol and hyaluronic acid; the resveratrol is loaded inside the mesoporous cerium dioxide, and the surface of the mesoporous cerium dioxide is modified with a hyaluronic acid layer.
2. The method for preparing the resveratrol composite material according to claim 1, characterized in that: The following steps are involved: The mesoporous cerium dioxide and the amino-containing modifier undergo a first grafting reaction to obtain amino cerium dioxide; The amination of cerium dioxide and resveratrol is subjected to a second grafting reaction to obtain a cerium dioxide / resveratrol composite material; The cerium dioxide / resveratrol composite material and hyaluronic acid are subjected to a third grafting reaction to obtain the resveratrol composite material.
3. The preparation method according to claim 2, characterized in that: The mesoporous cerium dioxide has a hollow structure.
4. The preparation method according to claim 2 or 3, characterized in that: The preparation method of mesoporous cerium dioxide comprises the following steps: The template, the dispersion stabilizer, the cerium source, the alkaline substance and water are mixed and pre-reacted to obtain a precursor; The precursor is sequentially calcined and etched to obtain the mesoporous cerium dioxide; The template includes silicon dioxide or carbon spheres; The dispersion stabilizer includes polyvinyl pyrrolidone or polyvinyl alcohol; The cerium source includes cerium nitrate or cerium acetate; The alkaline substance includes hexamethylenetetramine or ammonia water.
5. The preparation method according to claim 4, characterized in that: The temperature of the pre-reaction is 90-100° C., and the time is 1-3 hours; the temperature of the calcination is 500-700° C., and the insulation time is 2-3 hours; and the etching time is 18-24 hours.
6. The preparation method according to claim 2, characterized in that: The amino-containing modifier includes γ-aminopropyltriethoxysilane; The usage ratio of the mesoporous cerium dioxide and the amino-containing modifier is 50-300 mg: 1-2 mL; The first grafting reaction is carried out under reflux conditions, and the time of the first grafting reaction is 10 to 15 hours.
7. The preparation method according to claim 2, characterized in that: The mass ratio of the amino cerium dioxide to resveratrol is 2:1 ~ 5:1, the time of the second grafting reaction is 18 to 30 hours.
8. The preparation method according to claim 2, characterized in that: The mass ratio of the cerium oxide / resveratrol composite material to hyaluronic acid is 1:0.5 ~ 1:1.5, the time of the third grafting reaction is 18 to 24 hours.
9. The preparation method according to claim 2 or 8, characterized in that: The hyaluronic acid is used in the form of a hyaluronic acid activation solution, and the preparation method of the hyaluronic acid activation solution comprises the following steps: Mixing hyaluronic acid, EDC, NHS and water for activation to obtain the hyaluronic acid activation solution; The molar ratio of hyaluronic acid, EDC and NHS is 1:2:2; The activation temperature is room temperature and the activation time is 2 to 4 hours.
10. Use of the resveratrol composite material according to claim 1 or the resveratrol composite material prepared by the preparation method according to any one of claims 2 to 9 in the preparation of anti-inflammatory drugs.